The art of research report writing: An introduction for the beginners - Bunini Manyilizu (Mzumbe University, 2025)
The purpose of this handbook is to assist the report writer in building her or his competence through highlighting the important elements to consider when writing a research report, the skill is also helpful for better marks, scientific dissemination, credible recognition, and reflection of what transpired during the process as well as the results of her or his work and so on. This portable handbook is designed to assist different groups of learners in any discipline in both natural and social sciences and those in professional research, and in junior and middle class scientists. It is prepared as a quick reference for busy persons who might have no ample time for going through long paragraphs and descriptions in a constrained work schedule or setting. It is therefore in outlined format and where clarification was considered important then the description of the content was condensed to accommodate the needs of report writers. The objective of this work is to contribute in improving knowledge, skills and influencing a change for producing quality field work report; and findings which are useful and utilizable for solving problems. The book gives to learner’s overview instructions to follow in a process of writing a report and how the research proposal is manipulated to appear in research report. It highlights the guiding elements on what to include in which section of the research report including referencing styles, with examples.